Rural landscape as infrastructure: To see the invisible - Korandei Fedor S. (Крестьяноведение)
Review of the books: Vickery M.B. (2020) Landscape and Infrastructure: Reimagining the Pastoral Paradigm for the Twenty-First Century, London; New York; Oxford; New Delhi; Sydney: Bloomsbury Visual Arts; Mathews A. S. (2022) Trees Are Shape Shifters: How Cultivation, Climate Change, and Disaster Create Landscapes, London; New Haven: Yale University Press.